Effect of dietary manipulation on production, reproduction and immunocompetence traits in turkey breeder hens - BHATTACHARYYA, A; MAJUMDAR, S; BHANJA, S K; MANDAL, A B; DASH, B B; KADAM, M M (The Indian Journal of Animal Sciences, 2014)
Turkey breeder hens (200) and viable toms (24) of 30–35 weeks of age of small white variety were distributed into 2 treatment groups having 4 replicates of 25 hens and 3 toms in each treatment. First four replicates were offered turkey breeder diet (diet A) (NRC 1994) and other 4 replicates were offered high immune diet (diet B) having 115% amino acids, 1% each omega-6 and omega-3 fatty acids, retinol- 4.95 mg, DL-a-tocopherol- 199.86 mg, ascorbic acid –150 mg, selenium- 0.5 mg and zinc–118 mg / kg diet for 8 week duration. After 6 weeks of experimental feeding, 2 replicates from each treatment groups were vaccinated with ND (R2B) vaccine. Average egg weight of birds fed diet B was significantly higher after 6 weeks of experimental feeding than diet A. Per cent fertility and per cent hatchability on total egg set basis was better in the birds fed diet B than diet A. Chicks hatched from the birds fed diet B were heavier than the birds fed diet A. Total immunoglobulins, IgG and IgM response to sheep red blood cells were also higher in the diet B than diet A. Birds fed diet B had better cell-mediated immune response than birds fed diet A. Birds fed diet B had significantly higher HI titer against R2B vaccination than those fed diet A at 7 days post vaccination. Hence, it may be concluded that turkey breeders may be fed high immune diet to enhance egg weight, chick weight, fertility, hatchability and immune response.